A practical method for the ex-ante evaluation of land consolidation initiatives: Fully connected parcels with the same value. (February 2019) - Colombo, Sergio; Perujo-Villanueva, Manuel
Abstract: Land consolidation is an important instrument open to public authorities seeking to achieve sustainable rural development, especially in countries where rural property is highly fragmented. As land consolidation projects are complex and costly, researchers have tried to better understand the concepts and improve the methodologies involved so as to ensure their success. In this paper, we propose a methodology for assessing ex-ante the most suitable areas in which land consolidation initiatives could be carried out. The land in these areas must have a similar per hectare value and must be fully connected, criteria that make land consolidation projects much easier to implement. The case study focuses on olive groves in the Andalusia region. Olives are a perennial crop with a very fragmented, static property structure. Previous land consolidation projects have often had poor results mainly because of the reluctance of the affected landowners to get involved, due to difficulties in ensuring that the land allocated to them in the consolidation process had the same value as the land they owned prior to it. Our results indicate that a land consolidation procedure in the areas identified would bring about a noticeable improvement in the property structure and production cost savings of between 5.8% and 15.3% depending on whether the farm is worked by the family or by hired employees.